¿Existen diferentes comportamientos de los híbridos de maíz frente al carbón de la panoja? - De Rossi, Roberto Luis; Couretot, Lucrecia Alejandra; Astiz Gassó, Marta Mónica; García, J.; Masino, Alejandra; Samoiloff, Anabela; Guerra, Fernando Andrés; Labaque, M.; Plazas, Maria Cristina; Gregoret, C.; Guerra, Gustavo Dario (AAPRESID, 2024)
Poster